THE INFLUENCE OF PRICE PERCEPTION, SOCIAL MEDIA AND BRAND IMAGE ON REPURCHASE DECISIONS THROUGH CUSTOMER SATISFACTION INDOMIE GORENG ORIGINAL INSTANT NOODLES 84g AT TRIWIJAYA KEDAUNG STORE - Raden Mochammad Aldina Suryana; Rahayu Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the effect of price perceptions, Social Media, and Brand Image on Repurchase Decisions for Indomie Goreng Original 84g instant noodles at Triwijaya Kedaung Store, either directly or indirectly through Customer Satisfaction. The method used is quantitative with purposive sampling technique to determine a sample of 176 respondents. Data analysis using Structural Equation Modeling (SEM) with the AMOS Version 24 application. The study shows that price perception (p-value = 0.000) and Social Media (p-value = 0.000) have a significant positive effect on Customer Satisfaction, as well as Brand Image (p-value = 0.039). On Repurchase Decision, price perception has no significant effect (p-value=0.116), but Social Media (p-value=0.024) and Brand Image (p-value=0.018) have a significant positive effect. Customer satisfaction (p-value=0.006) has a significant positive effect on Repurchase Decisions. Indirectly through Customer Satisfaction, price perception (p-value=0.016) and Social Media (p-value=0.013) have a significant positive effect on Repurchase Decisions, not with Brand Image (p-value=0.108).